Vividhatīrthakalpaḥ : regards sur le lieu saint Jaina - Institut français de Pondichéry (Pondichery : Institut français de Pondichéry, Ecole française d'Extrême-Orient, 1995)
Study of the Kalpapradipa of Jinaprabha Suri, 14th cent., classical work on Jaina pilgrimage centre in the Indian subcontinent.
v. 1. Traduction et commentaire -- v. 2. Annexes.
Mode of access: Internet.
Keywords: Jinaprabha Sūri, -- active 14th century; Jaina pilgrims and pilgrimages -- India; Jaina shrines -- India